Poisoning by metals used in prosthetic materials in orthopedics and its current management - Farak Gomez, Juan; Villero Suárez, Jhonnier; Pérez GarcÃa, Mayurin; Rojas Pérez, Josselyn (Revista Cubana de Ortopedia y Traumatología, 2021)
Poisoning by metals present in prosthetic materials used in orthopedics is caused by the release of waste metals that are generated mainly by wear and corrosion. The objective of this study is to detail which are the current clinical and pathophysiological manifestations of the prosthetic metals used in orthopedics as well as the management of the most frequent arthroplasty associated with metal toxicity, hip arthroplasty, mentioning the most frequent metals that produce toxicity and implants or arthroplasties that carry a risk of developing intoxication. A narrative review was carried out through various databases from January 2005 to January 2021; the search and selection of articles were carried out in journals indexed in English. The results provided updated and organized information on the clinical and pathophysiological manifestations caused by the different types of frequent metals that produce toxicity present in prosthetic materials, as well as the management of hip arthroplasty.